2022
DOI: 10.1108/cr-03-2022-0029
|View full text |Cite
|
Sign up to set email alerts
|

Emerging HR analytics role in a crisis: an analysis of LinkedIn data

Abstract: Purpose This study aims to explore the emergence of the human resource (HR) analyst role. The job posts on LinkedIn display the industry demand and skills required by the organizations. This study identifies the different knowledge, skills and abilities (KSA) required for an HR analyst role in different stages of professional growth (i.e. entry-level, middle-senior level and top-level) across different industries/sectors as applicable to the crisis. Design/methodology/approach A total of 80 job posts were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…McCartney et al (2021) found that HR analysts should be familiar with various tools and technologies. Kashive and Khanna (2022) replicated this finding based on a review of 80 job posts from LinkedIn, 30 videos on YouTube, and interviews with HR professionals. Technical knowledge and skills required to use various programs, tools, and systems such as SQL (Structured Query Language), SAP (Systems, Applications & Products in Data Processing), HCM (Human Capital Management), Tableau, MIS (Management Information System), Python, R, Oracle, Java, SAS (Statistical Analysis System), HTML (HyperText Markup Language), Excel, BI (Business Intelligence), ERP (Enterprise Resource Planning), and HRIS (Human Resource Information System) are essential for HR analytics professionals on the job market.…”
Section: What Is the Current Knowledge Of People Analytics In Previou...mentioning
confidence: 63%
“…McCartney et al (2021) found that HR analysts should be familiar with various tools and technologies. Kashive and Khanna (2022) replicated this finding based on a review of 80 job posts from LinkedIn, 30 videos on YouTube, and interviews with HR professionals. Technical knowledge and skills required to use various programs, tools, and systems such as SQL (Structured Query Language), SAP (Systems, Applications & Products in Data Processing), HCM (Human Capital Management), Tableau, MIS (Management Information System), Python, R, Oracle, Java, SAS (Statistical Analysis System), HTML (HyperText Markup Language), Excel, BI (Business Intelligence), ERP (Enterprise Resource Planning), and HRIS (Human Resource Information System) are essential for HR analytics professionals on the job market.…”
Section: What Is the Current Knowledge Of People Analytics In Previou...mentioning
confidence: 63%
“…The study only considered three levels due to the limited time and the data availability. According to a study, the highest job post values were identified as 57%, 21%, and 20% for associate, entry, and mid-senior, respectively, in LinkedIn for human resource roles [29]. Another study [30] highlighted LinkedIn experience levels, but it considered three levels: entry, mid-level, and top-level (director and executive).…”
Section: Related Workmentioning
confidence: 99%
“…The job posts on LinkedIn display the industry demand and skills required by the organizations. Kashive and Khanna [24] study identified the different knowledge, skills, and abilities required for an HR analyst role in different stages of professional growth across different industries/sectors as applicable to the crisis [24].…”
Section: According To Marin and Nilămentioning
confidence: 99%